Physical, chemical and sensorial properties of healthy and mixture breads in Portugal - Rodrigues, Ângela (2014)
This study was conducted to characterize dif- ferent samples of regional bread made from mixed rye and wheat flours and healthy bread produced from a special formulation. The bread samples were evaluated in terms of their physical, chemical and sensory properties following the standard methods. The regional breads showed some differences in the chemical composition: Flor de Carregal had the highest protein content (14.59 %) and the lowest salt content (0.40 %), Pedregal had the highest fibre con- tent (0.89 %), and Pazurara was the richest in minerals (4.90 %). Although the sensory properties of bread samples were not statistically different, Flor de Cabanas obtained the highest overall acceptability among the samples (6.95 points). With respect to the healthy bread samples, slight differences were observed on their physical and sensory properties, which may attributed to their similarity in ingredient compositions. Furthermore, significant differ- ences were observed from the fiber, carbohydrate, protein and chloride contents of healthy bread samples. In com- parison with the two types of breads, it was found that they have different chemical, physical and sensory properties. Sensory analysis also showed that regional breads were more preferred by the panellists, with an average punctu- ation for global appreciation of 5.83 against 4.71.